A Multidisciplinary Approach and Review of Safety Recommendations for Plastic Surgeons during the COVID-19 Pandemic: Are N95 Masks Enough?. Issue 2 (27th July 2021) - Jalisi, Scharukh; Chen, Austin D.; Gomez, Ernest; Chigurupati, Radhika; Cauley, Ryan; Olbricht, Suzanne; Lee, Bernard T.; Lin, Samuel J.
Abstract : Summary: The novel coronavirus disease of 2019 pandemic presents a unique challenge to the field of plastic and reconstructive surgery. Although plastic surgeons may be postponing elective operations, there are still a number of emergent or urgent procedures that may need to be performed, and surgeons may be facing the reality of returning to a new normalcy of operating with coronavirus disease of 2019. These procedures, consisting of those such as head and neck reconstruction or maxillofacial trauma, largely require a multidisciplinary approach and may be considered of higher risk to health care workers because of the involvement of areas of the body identified as sources for viral transmission. Moreover, viral transmission may potentially extend beyond respiratory secretions, which has been the main focus of most safety precautions. The authors aim to present the scope of these procedures and the means of viral transmission, and to provide safety precaution recommendations for plastic surgery and its related disciplines.